2021
DOI: 10.3390/genes12091392
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins Syndrome: Genetics, Clinical Features and Management

Abstract: Treacher Collins syndrome (TCS) is associated with abnormal differentiation of the first and second pharyngeal arches, occurring during fetal development. Features of TCS include microtia with conductive hearing loss, slanting palpebral fissures with possibly coloboma of the lateral part of lower eyelids, midface hypoplasia, micrognathia as well as sporadically cleft palate and choanal atresia or stenosis. TCS occurs in the general population at a frequency of 1 in 50,000 live births. Four subtypes of Treacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Dauwerse The POLR1B gene encodes an RNA polymerase I subunit, and POLR1C and POLR1D encode common subunits between RNA polymerase I and III. [7][8][9] Moriwaki et al reported that primary ovarian insufficiency is caused by a heterozygous mutation in POLR2C (RNA Polymerase II Subunit C) that encodes DNAdirected RNA polymerase II subunit 3 (RPB3). 10 However, they did not report any symptoms associated with hearing loss in the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dauwerse The POLR1B gene encodes an RNA polymerase I subunit, and POLR1C and POLR1D encode common subunits between RNA polymerase I and III. [7][8][9] Moriwaki et al reported that primary ovarian insufficiency is caused by a heterozygous mutation in POLR2C (RNA Polymerase II Subunit C) that encodes DNAdirected RNA polymerase II subunit 3 (RPB3). 10 However, they did not report any symptoms associated with hearing loss in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dauwerse et al identified pathogenic variants in POLR1C and POLR1D , and Sanchez et al detected pathogenic variants in POLR1B in Treacher Collins patients. The POLR1B gene encodes an RNA polymerase I subunit, and POLR1C and POLR1D encode common subunits between RNA polymerase I and III 7‐9 …”
Section: Introductionmentioning
confidence: 99%
“…The extent of abnormalities varies with the severity of the disease. The classical features of TCS may include bilateral malar hypoplasia and mandibular hypoplasia with a prevalence of 81%-97%, coloboma of the lower lid in 54%-69% of the cases, downward slant palpebral fissure in 89%-100% of the cases, and malformation of the external, middle, and internal ear in 83%-92% of the cases [2]. Some of the most apparent symptoms are as follows: slanted eyes with notched lower eyelids and sunken cheekbones and jawbones, pointed nasal prominence, and a large mouth and a high-arched palate.…”
Section: Introductionmentioning
confidence: 99%
“…As the second most common craniofacial condition, microtia can occur as an isolated defect or in a spectrum of anomalies among a congenital syndrome. Most instances of microtia occur unilaterally and in the absence of a congenital syndrome; however, it is estimated that 20% to 60% of patients with microtia have overarching genetic syndromes such as craniofacial microsomia, oculo‐auriculo‐vertebral spectrum, Treacher Collins, DiGeorge, and more 3‐8 . Even in isolation, microtia is known to coincide with other cardiac, renal, vertebral, and thoracic defects, which present in up to 40% of microtia cases 6,8,9 .…”
mentioning
confidence: 99%
“…Most instances of microtia occur unilaterally and in the absence of a congenital syndrome; however, it is estimated that 20% to 60% of patients with microtia have overarching genetic syndromes such as craniofacial microsomia, oculo-auriculo-vertebral spectrum, Treacher Collins, DiGeorge, and more. [3][4][5][6][7][8] Even in isolation, microtia is known to coincide with other cardiac, renal, vertebral, and thoracic defects, which present in up to 40% of microtia cases. 6,8,9 These associations are likely explained by the abnormal migration of neural crest cells during embryological development, as these cells and their neuroepithelial precursors, specifically in the first and second branchial arches, contribute to the genesis of aural, cardiac, and vertebral structures.…”
mentioning
confidence: 99%